Excitatory glycine receptors control ventral hippocampus synaptic plasticity and anxiety-related behaviors - Lara Pizzamiglio; Elise Morice; Cécile Cardoso; Simon Bossi; Caroline Mailhes-Hamon; Moritz von Heimendahl; Gabrielle Girardeau; Pierre Paoletti (Proceedings of the National Academy of Sciences, 2025)
Excitatory glycine receptors (eGlyRs), composed of the glycine-binding NMDA receptor subunits GluN1 and GluN3A, have recently emerged as a novel neuronal signaling modality that challenges the traditional view of glycine as an inhibitory neurotransmitter. Unlike conventional GluN1/GluN2 NMDARs, the distribution and role of eGlyRs remain poorly understood. Here, we show that eGlyRs are highly enriched in the ventral hippocampus (VH) and confer distinct properties on this brain region. eGlyRs display a massive expression in both VH CA1 pyramidal cells and SST- and PV-positive interneurons, whereas in the dorsal hippocampus (DH) pyramidal cells lack these receptors. eGlyRs mediate excitatory tonic currents and control VH network excitability. They are also responsible for the attenuated long-term potentiation (LTP) in the VH compared with the DH, providing a molecular basis for this difference. Furthermore, eGlyRs are required for regulation of VH LTP by corticosterone, pointing to eGlyRs as mediators of the neuroendocrine stress response. Consistent with this pervasive influence in the ventral division of the hippocampus, eGlyRs contribute to the modulation of anxiety-related behaviors. Our work identifies eGlyRs as key players in VH circuitry and function, demonstrating their intimate association with brain regions that control internal states and emotional processing.